1.3 µm Quantum Dot‐Distributed Feedback Lasers Directly Grown on (001) Si. Issue 7 (8th June 2020) - Wan, Yating; Norman, Justin C.; Tong, Yeyu; Kennedy, M. J.; He, William; Selvidge, Jenny; Shang, Chen; Dumont, Mario; Malik, Aditya; Tsang, Hon Ki; Gossard, Arthur C.; Bowers, John E.
Abstract: Distributed feedback (DFB) lasers represent a central focus for wavelength‐division‐multiplexing‐based transceivers in metropolitan networks. Here, the first 1.3 µm quantum dot (QD) DFB lasers grown on a complementary metal‐oxide‐semiconductor (CMOS)‐compatible (001) Si substrate are reported. Temperature‐stable, single‐longitudinal‐mode operation is achieved with a side‐mode suppression ratio of more than 50 dB and a threshold current density of 440 A cm −2 . A single‐lane rate of 128 Gbit s −1 with a net spectral efficiency of 1.67 bits −1 Hz −1 is demonstrated, with an aggregate total transmission capacity of 640 Gbit s −1 using five channels in the O‐band. Apart from the QD active region growth, the overall fabrication is essentially identical to the commercial process for quantum well (QW) DFB lasers. This provides a process‐compatible path for QD technology into commercial applications previously filled by QW devices. In addition, the capability to grow laser epi across entire CMOS‐compatible (001) Si wafers adds extra benefits of reduced cost, improved heat dissipation, and manufacturing scalability. Through direct epitaxial integration of III–Vs and Si, one can envision a revolution of the photonics industry in the same way that CMOS design and processing revolutionize the microelectronics industry. This is discussed from a system perspective for on‐chip optical interconnects. Abstract : A simple, high‐yield process to make quantum dot‐based single frequency lasers is presented. Four big changes are highlighted: 1) growth on Si, 2) molecular beam epitaxy growth and regrowth which is possible to be implemented at 300 mm wafer scale, 3) a system demonstration without optical isolators, and 4) a path for Terabit transmitters with low‐cost and high‐volume is proposed.